The Determinant of Sharia Banking Performance through Financing to Deposit Ratio as Moderator - Ervina Rahmadila; Slamet Haryono (EkBis: Jurnal Ekonomi dan Bisnis, 2021)
The most concern for investors in both bank and non-bank institutions is the quality of the accounting information provided. Financial statements are considered important because they can determine decisions for each investor. Supporting performance in this era of globalization is accounting information system. Sharia banking's good performance is supported by several factors including capital or operational ratios such as CAR, BOPO, and NPF. This study used pooled least square method with panel data in the period 2010 to 2018. The results showed that together the results showed that the variables NPF, CAR, BOPO have a positive and insignificant influence on ROA.